EVALUASI KEPATUHAN PERAWAT DALAM MELAKUKAN ASSESSMENT ULANG NYERI MENGGUNAKAN CRITICAL PAIN OBSERB TOOL (CPOT) - Saputro, Heri; Anjarwati, Rina (STIKES Bethesda Yakkum, 2020)
ABSTRACT Background: Pain reassessment with CPOT in ICU of Bethesda Hospital was effectively carried out in 2018. The implementation has not been routinely carried out and only carried out by nine nurses from 19 ICU nurses; there for the internal audit results on the quality of nursing care about pain management in October 2018 was 51% of the target of 100%. Objective: To conduct a descriptive evaluation of nurses' compliance in re-assessing pain using CPOT in ICU of Bethesda Hospital in 2019. Method: This study used a qualitative design with a phenomenological approach and sampling with a purposive sampling approach. This research was conducted with interview techniques to five participants. Data analysis used thematic analysis. Results: The results of this study indicate the majority of nurses' knowledge have not understood the parameters and interpretations of pain reassessment assessment using CPOT. The behavior of nurses in reassessing pain using CPOT is not in accordance with the SPO, not all nurses are involved with personal constraints yet all understand the reassessment of pain using CPOT, forgetfulness, room hassles and lack of commitment. Supervision of the head of the room has not been done routinely. Conclusion: The implementation of pain reassessment using CPOT in ICU of Bethesda Hospital in 2019 was not in accordance with SPO, not all nurses were involved because not all nurses understood CPOT, forgot, room hassles, lack of nurse commitment and supervisory leadership had not been routinely done. Suggestion: Bethesda Hospital is suggested to revise the CPOT form, re-socialize the pain reassessment using CPOT for nurses and improve the surveillance system of the head and head of the room. Keywords: reassessment - CPOT – nurse compliance